DISTRIBUTION AND POPULATION STATUS OF HIMALAYAN MONAL PHEASANT (LOPH OPHORUSIMPEJANUS) I N SALKHALA GAME RESERVE, NEELUM VALLEY AZAD JAMMU AND KASHMIR (PAKISTAN) - B. Ahmad; F. Noor; M. S. Awan; R. A. Minhas; U. Ali (Journal of Animal and Plant Sciences, 2019)
Present study was carried out to determine distribution and population status of Himalayan Monal pheasant (Lophophorus impejanus) in Salkhala Game Reserve. This game reserve is an Endemic Bird Area in the Neelum valley within Western Himalayas, situated along ceasefire line between Pakistan and India. For data collection, study area was divided into three localities with eleven sub-localities. Systematic surveys were conducted in each sub-locality from March to September 2014, early in the morning (5:00-9:00am) and half an hour before evening. Distribution was determined by direct and indirect evidences including sighting, ground scratching, feathers, fecal material, foot prints, information collected from hunters, locals and wildlife staff. Populationof the bird was estimated by line transect method, laid down in the habitat of Himalayan Monal. The results indicated that this pheasant is distributed in all localities of the study area, preferring high altitude mountains with different aspects and slopes between 1900 mand 2600 m above sea level (asl). Overall population density of Himalayan Monal in the study area was 5.63 birds/km2. The highest density (6.81 birds/km2) was recorded in locality Khikhre-dohre, followed by locality Tehar-chhamman (5.33 birds/km2) and Chitta-pani (4.76 birds/km2). The sub-locality Dohre had highest population density (8.15 birds/km2) among eleven sub-localities.
Keywords: Himalayan Monal pheasant; Distribution; Population; Neelum valley; Salkhala Game Reserve; Azad Jammu